Doom's Law: Spaces of Sovereignty in Marvel's Secret Wars. Issue 1 (18th July 2017) - Curtis, Neal
Abstract : Sovereignty is both the foundation and source of law and the determination of the territory to which the law applies. In this latter sense, sovereignty and the law it supports are an explicitly spatial phenomenon, as can be seen in the meanings of the Greek word nomos, which aside from the law can also refer to a division that marks out a specific territory. This article posits that the Marvel crossover event entitled Secret Wars (2015, 2016) encapsulates the ways in which superhero comics might help us to understand the spatiality of sovereignty. It also considers how resistance to Doom's law was focused on the transgression of borders and the creation of alternative spatial arrangements.